2015
DOI: 10.1536/ihj.14-255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Transthyretin Combined With Mini Nutritional Assessment on Admission Provides Useful Prognostic Information in Patients With Acute Decompensated Heart Failure

Abstract: SummaryDecreased Transthyretin (TTR) can be observed in heart failure patients with malnutrition evaluated by the Mini Nutritional Assessment (MNA). This study investigated whether a combination of different nutritional assessment methods would be useful for assessing prognosis in patients with acute decompensated heart failure (ADHF).This prospective study included 52 patients with ADHF (mean age, 71.1 ± 14.7 years; men 55.8%) who were admitted to our hospital between June 2012 and August 2013. On admission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“… 27 In addition, there are significant correlations between nutritional scores (MSA, GNRI and CONUT) and both C reactive protein and natriuretic peptides in patients with decompensated HF. 28 Concordant with these findings, our data revealed that the group with more nutritional disturbance had higher mortality accompanied by higher levels of BNP, troponin I, C reactive protein, TNF-α, adiponectin, right-sided volume and pressure overload (ie, inferior vena cava diameter and TRPG). The same group had lower levels of haemoglobin and peak VO 2 , and these are reportedly prognostic factors of patients with HF.…”
Section: Discussionsupporting
confidence: 87%
“… 27 In addition, there are significant correlations between nutritional scores (MSA, GNRI and CONUT) and both C reactive protein and natriuretic peptides in patients with decompensated HF. 28 Concordant with these findings, our data revealed that the group with more nutritional disturbance had higher mortality accompanied by higher levels of BNP, troponin I, C reactive protein, TNF-α, adiponectin, right-sided volume and pressure overload (ie, inferior vena cava diameter and TRPG). The same group had lower levels of haemoglobin and peak VO 2 , and these are reportedly prognostic factors of patients with HF.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for this higher percentage was likely advanced age. It has been reported that malnutrition may be associated with poor outcomes in ADL in other diseases, such as cerebrovascular disorders [10,11,25,26], hip fracture [29,30], hospitalassociated deconditioning [31], and heart failure [32]. In those reports and the present study, ADL was found to improve if nutritional status improved.…”
Section: Discussionsupporting
confidence: 63%
“…These effects trigger systemic inflammation and cytokine generation, leading to several abnormalities of cardiomyocyte function and energetics . Interestingly, the Mini Nutritional Assessment revealed that 75% of patients with AHF had malnutrition or were at risk for malnutrition, suggesting this pathophysiology is highly prevalent …”
Section: Organ Systems Impacted By Congestion In Acute Heart Failure:mentioning
confidence: 99%
“…Circulating trimethylamine N‐oxide (TMAO), a gut‐derived metabolite, is associated with AHF and is predictive of death or rehospitalization. Transthyretin (prealbumin) provides prognostic information in combination with the Mini‐Nutritional Assessment in patients with AHF …”
Section: Clinical and Biochemical Assessments Of Acute Heart Failure mentioning
confidence: 99%